IMPLEMENTASI KEBIJAKAN PENGADAAN BUS SEKOLAH GRATIS BAGI PELAJAR DI KECAMATAN MANDAU KABUPATEN BENGKALIS - ", Mentari; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
These day Transportation technology experienced development as well the increasing human needs for transportation but it’is not followed with increasing the amount of transportation facility which is public transportation, one of the kind is in Sub-district Mandau District Bengkalis where in the end causes so many underage students brave enough to ride motorized vehicle to school caused by there is no public transportation onto their school and this problem causes students become contributor for traffic incident and violation number annually causes UPTD Perhubungan Sub-district Mandau-Pinggir in the end provides procurement free school bus to eases the student go to their school and decrease the usage amount of motorized vehicle of underage student, based on that the researcher is interested to evaluate how the implementation of free school bus procurement policy for students in Sub-district Mandau District Bengkalis. Theoretical concept used is implementation based from George C. Edward III, which is said that in public policy implementation contains 4 variables; communication, resources, disposition/behavior of the executor and bureaucracy structure. The purpose of this research is to analyze how the implementing and what factors that affect the implementation of free school bus procurement policy for students in Sub-district Mandau District Bengkalis. This research uses qualitative method with illustrate and explain the existence problem with answers and problems based of facts that existed. In collecting data, researcher use methods of interview, observation, and documentation with snowball sampling method as the source of information and data analyzing with descriptive qualitative method. The research result showed that the execution of the implementation of free school bus procurement policy for students in Sub-district Mandau District Bengkalis has been completed although it has not been effective yet, this is caused by the limit of facilities and infrastructures where the amount of bus fleets not yet adequate, funds limited, and community customs in dicipline.Keyword: Implementation, Procurement Policy, School Bus